1997
DOI: 10.1071/aj96028
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotopes, Kerogen Types and the Permian-Triassic Boundary in Australia: Implications for Exploration

Abstract: A global stratotype section for the boundary between the Permian and Triassic Systems is yet to be agreed internationally. However, in many parts of the world, there is evidence of massive extinction of marine fauna at or near the P-T boundary. In the absence of marine fauna, as is the case in most of Australia, changes in plant microfossils, in carbon isotopic signatures, and radiometric dates using SHRIMP, have been used to mark the boundary. The leading questions which arise from this are whether these even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 0 publications
3
39
0
Order By: Relevance
“…In recent years there has been a tendency, partly on the basis of carbon isotope abundance variations (e.g., Morante et al 1994;Morante 1996), to place it within the P. microcorpus Zone (sensu Helby et al 1987). But Foster and coworkers (e.g., Foster et al 1997Foster et al , 1998 have concluded that these carbon isotope changes in part reflect fluctuating relative abundances of woody and non-woody derived kerogen, which in turn are due to changes in sedimentary facies that are not necessarily globally correlative. We concur with Foster et al (1997Foster et al ( , 1998 in discounting the correlative value of the carbon isotope data.…”
Section: Appendixmentioning
confidence: 99%
“…In recent years there has been a tendency, partly on the basis of carbon isotope abundance variations (e.g., Morante et al 1994;Morante 1996), to place it within the P. microcorpus Zone (sensu Helby et al 1987). But Foster and coworkers (e.g., Foster et al 1997Foster et al , 1998 have concluded that these carbon isotope changes in part reflect fluctuating relative abundances of woody and non-woody derived kerogen, which in turn are due to changes in sedimentary facies that are not necessarily globally correlative. We concur with Foster et al (1997Foster et al ( , 1998 in discounting the correlative value of the carbon isotope data.…”
Section: Appendixmentioning
confidence: 99%
“…Foster et al (1997) determined facies and organic models based on isotopic and chemical composition of organic carbon from E and W Australian basin examples.…”
Section: Paleoenvironmental Indicatorsmentioning
confidence: 99%
“…At high paleolatitude of the Southern hemisphere, in Western and Eastern Australian, carbon isotope profiles also exhibit a high magnitude drop in δ 1 3 Corg values. However, Foster et al (1997) concluded that the isotopic values of organic carbon are strongly influenced by the primary source of the organic matter and questioned their use in chemostratigraphic correlations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Permian wood shows heavier carbon isotope values than coeval marine organic matter (Faure et al 1995;Foster et al 1997;Korte et al 2001). Changes in the amount of terrestrial organic matter in marine sediments probably impacted the negative carbon-isotope shift in Australian PTB successions (Morante 1996;Foster et al 1997;Thomas et al 2004).…”
mentioning
confidence: 99%
“…For instance, Permian wood shows heavier carbon isotope values than coeval marine organic matter (Faure et al 1995;Foster et al 1997;Korte et al 2001). Changes in the amount of terrestrial organic matter in marine sediments probably impacted the negative carbon-isotope shift in Australian PTB successions (Morante 1996;Foster et al 1997;Thomas et al 2004). To complicate matters, ocean anoxia was widespread in the latest Permian oceans (e.g., Wignall & Hallam 1992;Kajiwara et al 1994;Isozaki 1997;Algeo et al 2008;Grasby & Beauchamp 2009) reaching even shallow water depths, as traced by green sulphur bacteria (¼ Chlorobiaceae) in the PTB Hovea-3 core from W-Australia (Grice et al 2005).…”
mentioning
confidence: 99%